Genome‐wide association study of multiethnic nonsyndromic orofacial cleft families identifies novel loci specific to family and phenotypic subtypes. Issue 3 (22nd February 2022) - Mukhopadhyay, Nandita; Feingold, Eleanor; Moreno‐Uribe, Lina; Wehby, George; Valencia‐Ramirez, Luz Consuelo; Restrepo Muñeton, Claudia P.; Padilla, Carmencita; Deleyiannis, Frederic; Christensen, Kaare; Poletta, Fernando A.; Orioli, Ieda M.; Hecht, Jacqueline T.; et al.
Abstract: Nonsyndromic orofacial clefts (OFCs) are among the most common craniofacial birth defects worldwide, and known to exhibit phenotypic and genetic heterogeneity. Cleft lip plus cleft palate (CLP) and cleft lip only (CL) are commonly combined together as one phenotype (CL/P), separately from cleft palate alone. In comparison, our study analyzes CL and CLP separately. A sample of 2218 CL and CLP cases, 4537 unaffected relatives of cases, and 2673 pure controls with no family history of OFC were selected from the Pittsburgh Orofacial Cleft (Pitt‐OFC) multiethnic study.genome‐wide association studies were run for seven specific phenotypes created based on the cleft type(s) observed within these families, as well as the combined CL/P phenotype. Five novel genome‐wide significant associations, 3q29 (rs62284390), 5p13.2 (rs609659), 7q22.1 (rs6465810), 19p13.3 (rs628271), and 20q13.33 (rs2427238), and nine associations ( p  ≤ 1.0E−05) within previously confirmed OFC loci— PAX7, IRF6, FAM49A, DCAF4L2, 8q24.21, ARID3B, NTN1, TANC2 and the WNT9B:WNT3 gene cluster—were observed. We also found that single nucleotide polymorphisms within a subset of the associated loci, both previously known and novel, differ substantially in terms of their effects across cleft‐ or family‐specific phenotypes, indicating not only etiologic differences between CL and CLP, but also genetic heterogeneity within each of the two OFC subtypes.